PERANCANGAN E-BUSINESS PADA USAHA MIKRO KECIL MENENGAH ECOPRINT RAMBAN AYU - Indira Aulia; Sudharmawan Ogi P.; Putri Anggun Z (Journal of Computer Science and Technology, 2023)
The design of e-business for micro, small and medium enterprises on Ecoprint Ramban Ayu products is based on the inadequate marketing distribution system for ecoprint products located on Jl. MT. Haryono no. 100 Pandean, Temanggung, Jawa Tengah which does not yet have a standardized and user-friendly application. So that this research contains a application design that has been adapted to the Ramban Ayu Ecoprint business and business industry digitalization standards, especially in the fashion sector, providing various display features that make it easier for prospective customers to find products and process transactions. In addition, this research also presents a SWOT design and PEST analysis that every business wants to develop must have. The conclusion of this study is to produce a application design display, explore strengths, weaknesses, business potential, threats, long-term business strategies, and aspects that can drive business development quickly, namely by utilizing various business policies from government, economic, social to technology.